Superb energy density in biomass-based nanocomposites with ultralow loadings of nanofillers - Xiang Yu; Chenyi Li; Li Li; Minghai Yao; Hanxiao Gao; Yuquan Liu; Ze Yuan; Shengfei Tang; Quan Luo; Haibo Zhang; Yang Liu; Huamin Zhou (Journal of Materiomics)
Biomass dielectric polymers hold promise in developing renewable and biodegradable capacitive energy storage devices. However, their typical discharged energy density remains relatively low (<20 J/cm3) compared to other existing synthetic polymers derived from petroleum sources. Here a greatly enhanced discharged energy density is reported in diluted cyanoethyl cellulose (CEC) nanocomposites with inclusion of ultralow loadings (0.3%, in volume) of 30 nm sized TiO2 nanoparticles. Owing to the interfacial polarization introduced by interface, the composite of 0.3% exhibits a large dielectric constant of 29.2 at 1 kHz, which can be described by interphase dielectric model. Meanwhile, the introduction of nanofillers facilitate the formation of deeper traps impeding electrical conduction in CEC, which results in an ultrahigh breakdown strength of 732 MV/m. As a result, a remarkable discharged energy density of 12.7 J/cm3 with a charge-discharge efficiency above 90% is achieved, exceeding current ferroelectric-based and biomass-based nanocomposites. Our work opens a novel route for scalable biomass-based dielectrics with high energy storage properties.